Potentially harmful elements and health risk assessment in groundwater of urban industrial areas - Ishtiaq, Muhammad; Khan, Muhammad Jibran; Khan, Said Akbar; Ghani, Junaid; Ullah, Zahid; Nawab, Javed; Alrefaei, Abdulwahed Fahad; Almutairi, Mikhlid H.; Alharbi, Sultan N. (Frontiers in Environmental Science, 2024)
Groundwater quality was investigated in three urban semi-arid multi-industrial metropolitan areas i.e. (Hayatabad Industrial Estate, Peshawar (HIEP), Gadoon Industrial Estate, Swabi (GIES) and Hattar Industrial Estate, Haripur (HIEH). The main aim of the study was to determine their physicochemical parameters, potentially harmful elements (PHEs) concentration, pollution sources and public health risks in semi-arid multi-industrial metropolitan areas of Khyber Pakhtunkhwa (KPK), Pakistan. The physicochemical parameters (pH, TDS and EC), PHEs (Cd, Zn, Pb, Cr and Ni) concentrations and Mg in drinking water sources were found within the permissible limits, except Fe, which exceeded the World Health Organization (WHO) acceptable limit. Among PHEs, Zn had the highest contribution rates of 69.6%, 58.2% and 67.64% in HIEP, GIES and HIEH, respectively, while Cd showed the lowest contribution rates (3.15%, 1.98% and 2.06%) for HIEP, GIES and HIEH respectively. Principal component analysis (PCA) showed significant correlations between parameters, with contributions of industrial effluents and wastewater discharge (46.81%), mixed sources (34.05%) and geo-genic sources (19.14%) for drinking water in the study area. The carcinogenic risk (CR) for Cd, Cr, Ni and Pb, were found within the acceptable threshold value of 1 × 10 -4 . This study suggests that urban groundwater should also be regularly monitored for PHEs contamination as over-extraction, industrialization and informal E-waste recycling events surges the public health risks globally, facing related environmental contamination difficulties of the urban groundwater.